2022
DOI: 10.26508/lsa.202201609
|View full text |Cite
|
Sign up to set email alerts
|

De novo discovery of traits co-occurring with chronic obstructive pulmonary disease

Abstract: Chronic obstructive pulmonary disease (COPD) is a heterogeneous group of chronic lung conditions. Genome-wide association studies have identified single-nucleotide polymorphisms (SNPs) associated with COPD and the co-occurring conditions, suggesting common biological mechanisms underlying COPD and these co-occurring conditions. To identify them, we have integrated information across different biological levels (i.e., genetic variants, lung-specific 3D genome structure, gene expression and protein–protein inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…Potential co-occurring traits were identified using the Multimorbid3D pipeline (Golovina et al 2023;Zaied et al 2023) (https://github.com/Genome3d/multimorbid3D). The 576 autismassociated SNPs underwent a linkage disequilibrium analysis to determine those in LD (r 2 = 0.8, width = 5000 bp; supplementary table S2).…”
Section: Identifying Possible Co-occurring Traits Of Autismmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential co-occurring traits were identified using the Multimorbid3D pipeline (Golovina et al 2023;Zaied et al 2023) (https://github.com/Genome3d/multimorbid3D). The 576 autismassociated SNPs underwent a linkage disequilibrium analysis to determine those in LD (r 2 = 0.8, width = 5000 bp; supplementary table S2).…”
Section: Identifying Possible Co-occurring Traits Of Autismmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted April 26, 2023. ; https://doi.org/10. 1101 To investigate the interconnectivity of complex polygenic traits, network-based analyses have been previously used by our group (Golovina et al 2023). In this study, we identified causative and pleiotropic genes that are affected by SNPs associated with both autism and other traits within cortical gene regulatory networks (GRNs) at two different developmental stages.…”
mentioning
confidence: 99%
“…It was estimated that the global prevalence of COPD is 10.3% (Adeloye et al., 2022). More than 3.2 million people die from COPD annually, and it is the third leading cause of death worldwide (Golovina et al., 2022; Lu et al., 2022). With the development of medical technology, the survival rate of COPD patients is increasing year by year (Collaborators., 2016; Dong et al., 2021; Lash et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…genetic risk, chromatin structure, protein interactions and phenotypes) to inform on the mechanistic interactions that impact on shared inherited genetic risk. We have developed a de novo analytical approach that uses Protein-Protein Interaction Networks (PPIN) to identify connections across these levels [14][15][16][17] . The use of tissue-speci c Gene Regulatory Networks (GRN) within this integrative approach identi es conditions/traits co-occurring with PD, and the genetic variation and biological pathway(s) that is responsible for the observed cooccurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we performed an unbiased, de novo analysis 14,15,17,18 integrating the Brain Cortex-speci c Gene Regulatory Network (BC-GRN), PPIN and GWAS data. We identify genes expressed in the brain cortex that are causally related to PD.…”
Section: Introductionmentioning
confidence: 99%